Eco-friendly zinc oxide nanoparticle biosynthesis powered by probiotic bacteria - AL-Tameemi, Ahmed Issa; Masarudin, Mas Jaffri; Abdul Rahim, Raha; Mizzi, Rachel; Timms, Verlaine J.; Mat Isa, Nurulfiza; Neilan, Brett A. (Springer Science and Business Media Deutschland GmbH, 2025)
Abstract: The rapid advancement of nanotechnology, particularly in the realm of pharmaceutical sciences, has significantly transformed the potential for treating life-threatening diseases. A pivotal aspect of this evolution is the emergence of “green nanotechnology,” which emphasizes the environmentally sustainable synthesis of raw materials through biological processes. This review focuses on the biological synthesis and application of zinc oxide (ZnO) nanoparticles (NPs) from probiotic bacteria, particularly those sourced from wastewater. Microorganisms from wastewater tolerate harmful elements and enzymatically convert toxic heavy metals into eco-friendly materials. These probiotic bacteria are instrumental in the synthesis of ZnO NPs and exhibit remarkable antimicrobial properties with diverse industrial applications. As the challenge of drug-resistant pathogens escalates, innovative strategies for combating microbial infections are essential. This review explores the intersection of nanotechnology, microbiology, and antibacterial resistance, highlighting the importance of selecting suitable probiotic bacteria for synthesizing ZnO NPs with potent antibacterial activity. Additionally, the review addresses the biofunctionalization of NPs and their applications in environmental remediation and therapeutic innovations, including wound healing, antibacterial, and anticancer treatments. Eco-friendly NP synthesis relies on the identification of these suitable microbial “nano-factories.” Targeting probiotic bacteria from wastewater can uncover new microbial NP synthesis capabilities, advancing environmentally friendly NP production methods. Key points: • Innovative strategies are needed to combat drug-resistant pathogens like MRSA. • Wastewater-derived probiotic bacteria are an eco-friendly method for ZnO synthesis. • ZnO NPs show significant antimicrobial activity against various pathogens.